ICICI Prudential: challenges in reaching the last mile. Issue 4 (27th November 2020) - Das, Parthasarathi; Moharana, Tapas Ranjan; Indibara, Indirah
Abstract : Learning outcomes: The specific learning objectives of the case are as follows: To contribute to the knowledge of environmental challenges faced by various financial companies while trying to foray into the rural markets, especially in case of insurance products' expansion strategy; to understand the distribution strategy adopted by insurance companies in rural as well as urban markets; to apply the concepts such as mental accounting, designing and pricing of insurance products to develop an effective strategy for insurance products targeting the rural market; to be able to analyse the data available on products and the rural market structure that enables the students to derive from an implementable managerial framework and design an effective rural market strategy for insurance products; and to enable the students to evaluate the key rural market drivers, which will subsequently help them to develop a new structure of rural distribution channel. Case overview/synopsis: ICICI Prudential Life Insurance Company Limited (IPRU) was trying to reach the last mile customers of rural India to tap the opportunity and meet the Indian Government's statutory requirement of financial inclusion. Even though the leadership of IPRU was optimistic about the untapped potential of rural India, and launched a separate business vertical - Rural Business Channel (RBC) in the year 2002 to cater to this target segment, yet it faced many strategic issues while foraying into the rural domain. The company struggled with both the designing of products as per the rural customers' needs, as well as the distribution of these products in rural areas. The present case study is an attempt to bring out the strategic challenges that were faced by the IPRU management, with a major focus on designing, pricing and distribution of rural insurance products. The case study will help the readers in understanding what might go wrong while entering new rural markets and how to deal with these challenges. Complexity academic level: The case study can be used to teach both undergraduate and postgraduate management students. Supplementary materials: Teaching Notes are available for educators only. Subject code: CSS 8: Marketing.